Mangrove Community Structure on the North Coast of Bengkalis Island, Riau Province - Rahman, Muhammad Aulia; Efriyeldi, Efriyeldi; Nasution, Syafruddin (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
This research was conducted in April 2022 on the North Coast of Bengkalis Island, Riau Province. The purpose of this study was to determine the structure of the mangrove community on the North Coast of Bengkalis Island, Riau Province. The method used in this study is a survey method, through direct observation in the field (in situ). Determination of research stations was carried out by purposive sampling method, the research location was divided into 3 stations then the stations were divided into 3 transects and 3 plots were placed on each transect. The results showed that the mangrove species found consisted of 8 species. The highest density of mangroves in the tree category was at station I, namely 1,767 ind/ha, the highest density of mangroves in the sapling category was at station I, namely 3,645 ind/ha. The species with the highest density, both from the category of trees and saplings, is R. apiculata. The diversity index belongs to the medium category (H' = 1.49 - 1.69) which means that the mangrove community is experiencing significant pressure (disorder). The uniformity index value obtained is in the high category (E = 0.89 - 0.90) where the distribution of species in these waters is in a balanced state. The dominance index value (C = 0.18 - 0.26) indicates that there are no species that dominate in these waters